FEATURES OF THE ADMINISTRATIVE-TERRITORIAL DIVISION OF THE MOUNTAIN ZONE OF UZBEKISTAN AND THEIR IMPROVEMENT (Scientific journal of the Fergana State University, 2025)
The article reveals the historical and geographical aspects of the administrative-territorial division of the mountainous zone of the Republic of Uzbekistan. The characteristics of the formation of administrative units of mountainous regions, changes in their numbers and factors influencing these changes are given.